Utilization of multiple genetic methods for prenatal diagnosis of rare thalassemia variants - Jiang, Fan; Zhou, Jianying; Zuo, Liandong; Tang, Xuewei; Li, Jian; Li, Fatao; Yang, Tianhe; Qu, Yanxia; Wan, Junhui; Liao, Can; Li, Dongzhi (Frontiers in Genetics, 2023)
Background: Thalassemia is the most prevalent monogenic disorder caused by an imbalance between the α-and β-globin chains as a result of pathogenic variants in the αor β-globin genes. Novel or complex structural changes in globin genes are major hurdles for genetic consulting and prenatal diagnosis. Methods: From 2020 to 2022, genetic analysis was performed on 1316 families suspected of having children with thalassemia major, including 42 pregnant couples suspected of being thalassemia carriers with rare variants. Multiple techniques including multiplex ligationdependent probe amplification (MLPA), Sanger sequencing, targeted next-generation sequencing, and single-molecule real-time (SMRT) sequencing were used to diagnose rare thalassemia.Results: The rate of prenatal diagnosis for rare thalassemia variants was 3.19% (42/1316). The most prevalent alleles of α-and β-thalassemia are Chinese G γ( A γδβ) 0 and --THAI deletion. In addition, ten rare complex genotypes include one Chinese G γ( A γδβ) 0 deletion combined with HBG1-HBG2 fusion, two rare deletions at HBB gene (hg38, Chr11: 5224211-5232470, hg38, Chr11: 5224303-5227790), one complete 7412 bp fusion gene for Anti lepore Hong Kong, two complex rearrangements of the α-globin gene cluster, two novel duplications, and two rare large deletions in the α-globin gene cluster.Accurate gene diagnosis for probands with combined molecular biology techniques is the key to prenatal diagnosis of rare thalassemia. 2